2020
DOI: 10.3390/ijerph17186473
|View full text |Cite
|
Sign up to set email alerts
|

Interference and Impact of Dysmenorrhea on the Life of Spanish Nursing Students

Abstract: Dysmenorrhea is a cause of absenteeism in universities which, in the context of nursing studies, may affect mandatory attendance. Moreover, presenteeism is associated with medication errors, patient falls, and a reduced quality of patient care. This study sought to identify the degree of interference of dysmenorrhea on daily life and its impact on academic performance among Spanish nursing students, and to explore the reasons for presenteeism. A cross-sectional descriptive study was conducted on 261 nursing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 39 publications
(68 reference statements)
3
22
0
4
Order By: Relevance
“…Our findings regarding restrictions on daily activities and sports coincide with the results of Abreu-Sánchez et al [2], who found that menstrual pain accounted for 62.8% of absenteeism among Spanish female university students and that certain daily activities caused or intensified their menstrual pain. These included siting down, walking and having a full bladder.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our findings regarding restrictions on daily activities and sports coincide with the results of Abreu-Sánchez et al [2], who found that menstrual pain accounted for 62.8% of absenteeism among Spanish female university students and that certain daily activities caused or intensified their menstrual pain. These included siting down, walking and having a full bladder.…”
Section: Discussionsupporting
confidence: 91%
“…In the field of nursing, presenteeism has been identified as a risk to patient safety due to possible errors in the administration of medication [50,51]. The motives for presenteeism when suffering from menstrual pain may include [2]: students considering menstrual pain as an insufficient reason to be absent, thinking that others do not consider it a valid justification to be absent, anxiety about the negative academic impact of being absent, believing that attending class despite feeling unwell is most responsible, and feelings of guilt when being absent. In Spain, nursing students displayed a 92.7% level of presenteeism due to dysmenorrhea [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations